Performance evaluation of the Becton Dickinson Kiestra™ IdentifA/SusceptA. (August 2021) - Jacot, Damien; Sarton-Lohéac, Garance; Coste, Alix T.; Bertelli, Claire; Greub, Gilbert; Prod'hom, Guy; Croxatto, Antony
Abstract: Objectives: New automated modules are required to provide fully automated solutions in diagnostic microbiology laboratories. We evaluated the performance of a Becton Dickinson Kiestra™ IdentifA/SusceptA prototype for MALDI-TOF identification (ID) and Phoenix™ antibiotic susceptibility testing (AST). Methods: The performance of the IdentifA/SusceptA coupled prototype was compared with manual processing for MALDI-TOF ID on 1302 clinical microbial isolates or ATCC strains and for Phoenix™ M50 AST on 484 strains, representing 61 species. Results: Overall, the IdentifA exhibited similar ID performances than manual spotting. Higher performances were observed for Gram-negative bacteria with an ID at the species level (score >2) of 96.5% (369/382) and 86.9% (334/384), respectively. A significantly better performance was observed with the IdentifA (95.2%, 81/85) compared with manual spotting (75.2%, 64/85) from colonies on MacConkey agar. Contrariwise, the IdentifA exhibited lower ID performances at the species level than manual processing for streptococci (76.1%, 96/126 compared with 92%, 115/125), coagulase-negative staphylococci (73.3%, 44/60 compared with 90%, 54/60) and yeasts (41.3%, 19/46 compared with 78.2%, 36/46). Staphylococcus aureus and enterococci were similarly identified by the two approaches, with ID rates of 92% (65/70) for the IdentifA and 92.7%, (64/69) for manual processing and 94.8%, (55/58) for the IdentifA and 98.2%, (57/58) for manual processing, respectively. The SusceptA exhibited an AST overall essential agreement of 98.82% (6863/6945), a category agreement of 98.86% (6866/6945), 1.05% (6/570) very major errors, 0.16% (10/6290) major errors, and 0.91% (63/6945) minor errors compared to the reference AST. Conclusions: Overall, the automated IdentifA/SusceptA exhibited high ID and AST performances.